The taxonomy and nomenclature of Kalanchoe ×kewensis [K. bentii × K. glaucescens] (Crassulaceae subfam. Kalanchooideae), a nothospecies produced at the Royal Botanic Gardens, Kew, in the early 1900s - Smith, Gideon F. (Phytotaxa, 2023)
The taxonomy and nomenclature of Kalanchoe ×kewensis (Crassulaceae subfam. Kalanchooideae) [hybrid formula: K. bentii × K. glaucescens], an old but widely available hybrid artificially produced at the Royal Botanic Gardens, Kew, in the early 1900s, are discussed and clarified. The two independently validly published names K. ×kewensis Watson and K. ×kewensis N.E.Br. are neotypified and lectotypified, respectively, to make the latter an illegitimate homonym of the former. An amplified description is provided for the nothospecies, and it is illustrated.